WATER-SOLUBLE POLYMERIC IONIC 5-FLUOROURACIL COMPLEX BASED ON METHACRYLIC ACID COPOLYMERS - Zhukova, OLGA V.; RYABOV, SERGEY A.; ZAITSEV, SERGEY D.; KUZNETSOVA, OLGA V.; GAVRILOVA, DARIA M.; ARCHIPOVA, EUGENIA V.; GOLOVACHEVA, ANNA A.; VOLKOVA, YULIA S. (International Journal of Applied Pharmaceutics, 2019)
Objective: The objective of this work was to obtain a water-soluble 5-fluorouracil (5-FU) polymeric complex on the basis of a methacrylic acid (MAA) copolymer to be used as an injectable chemotherapeutic agent. Methods: A polymeric carrier was synthesized using tert-butyl methacrylate (TBMA) as a monomer, thioglycolic acid, and azobisisobutyronitrile as a radical polymerization initiator. The polymer was converted by acid hydrolysis into a water-soluble copolymer of TBMA and MAA of 20: 80 mass%, respectively. The copolymer of TBMA and MAA was modified with 5-FU. Their formation was proved using IR and UV spectroscopy. The particle size of the 5-FU polymeric complex was estimated by turbidimetry, which is based on measuring the intensity of light transmitted through a disperse system. The release of 5-FU from the obtained ionic complexes by dialysis in vitro was evaluated. Results: Polymeric carriers were obtained with different amounts of 5-FU (5, 15, 25, 50 mol%). A high peak at λ = 266 nm was observed in the UV spectrum of the polymeric carrier (characteristic of 5-FU). The particle size was estimated at 13 nm for the complex with 5 mol% 5-FU and 26.8 n for the complex with 50 mol% 5-FU. The 5-FU release was estimated in two parallel experiments at 37 °C. One utilized a phosphate-citrate buffer with pH 5.0 to model the intracellular space and the other, a phosphate buffer with pH 7.4 to model the intravascular space. Two systems, with 5 and 15 mol% 5-FU, were chosen for testing. In both phosphate buffer and phosphate-citrate buffer, 5-FU was released from the polymeric complex with 5 mol% 5-FU approximately 1.3 times faster than from the complex containing 5 mol% 5-fluorouracil. The kinetics of 5-FU release from the polymeric complex (5 mol% 5-fluorouracil) showed that the 5-FU release was 77.9% in phosphate-citrate buffer and 59.6% in phosphate buffer over 52 h of dialysis. When the 5-FU release kinetics was studied with the polymeric complex containing 15 mol% 5-FU, the 5-FU release was 100.0% in phosphate-citrate buffer and 75.1% in phosphate buffer over 57 h of dialysis. Conclusion: Water-soluble nanoscale complexes of 5-FU with TBMA–MAA copolymers extend application of 5-FU, while its general toxicity might be lower. The complexes are sufficiently stable at pH 7.4 and readily release 5-FU at pH 5.0.